2002
DOI: 10.1124/jpet.102.034322
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological Characterization of Ro 63-1908 (1-[2-(4-Hydroxy-phenoxy)-ethyl]-4-(4-methyl-benzyl)-piperidin-4-ol), a Novel Subtype-SelectiveN-Methyl-d-Aspartate Antagonist

Abstract: Ro 63-1908, 1-[2-(4-hydroxy-phenoxy)-ethyl]-4-(4-methyl-benzyl)-piperidin-4-ol, is a novel subtype-selective N-methyl-D-aspartate (NMDA) antagonist that has been characterized in vitro and in vivo. Ro 63-1908 inhibited [ 3 H]dizocilpine ( 3 H-MK-801) binding in a biphasic manner with IC 50 values of 0.002 and 97 M for the high-and low-affinity sites, respectively. Ro 63-1908 selectively blocked recombinant receptors expressed in Xenopus oocytes containing NR1C ϩ NR2B subunits with an IC 50 of 0.003 M and tho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
23
1

Year Published

2003
2003
2016
2016

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(27 citation statements)
references
References 34 publications
(46 reference statements)
3
23
1
Order By: Relevance
“…8 A). We also evaluated 1 g/0.5 l (5.0 mM) Ro 63-1908 (IC 50 ϭ 0.003 M) (Gill et al, 2002), another NR2B inhibitor (Gill et al, 2002;Higgins et al, 2003) and obtained similar results (n ϭ 5 mice) (Fig. 8 A).…”
Section: Behavioral Nociceptive Studies Of Nr2b Receptor Antagonistssupporting
confidence: 49%
“…8 A). We also evaluated 1 g/0.5 l (5.0 mM) Ro 63-1908 (IC 50 ϭ 0.003 M) (Gill et al, 2002), another NR2B inhibitor (Gill et al, 2002;Higgins et al, 2003) and obtained similar results (n ϭ 5 mice) (Fig. 8 A).…”
Section: Behavioral Nociceptive Studies Of Nr2b Receptor Antagonistssupporting
confidence: 49%
“…Indeed, the NR2B antagonist Ro 25-6981 had antidepressant-like properties in the forced swim test (Maeng et al, 2007). From a safety perspective, this compound also has not been associated with vacuolization in rodents (Gil et al, 2002), in contrast to the reversible vacuolization at high doses observed with noncompetitive NMDA antagonists such as ketamine and dizocilpine (Olney et al, 1989).…”
Section: Nmda Receptor Antagonists (Major Depressive Disorder and Bipmentioning
confidence: 99%
“…These transgenic mice showed an enhanced behavioral response to hindpaw inflammation, suggesting a role of NR2B subunits in prolonged models of peripheral inflammation (Wei and others 2001;Miki and others 2002). The in vivo antinociceptive action of selective NR2B antagonism was demonstrated by two compounds, Ro63-1908 (benzyl-piperidinyl-4-ol) and CP101,606 (an ifenprodil analog) (Chazot and others 2002;Gill and others 2002). Furthermore, flupirtinmaleate (Katadolon ® ) was discussed as an NMDA receptor antagonist (Muller and others 1996;Seyfried and others 2000), and studies on human brain slices also showed that flupirtinmaleate is neuroprotective.…”
Section: Neurodegeneration: Alzheimer's Disease Amyotrophic Lateral mentioning
confidence: 99%
“…Specific receptor blockers of the NMDA receptor are thought to selectively interrupt the excitotoxic process after ischemia. Chazot and others (2002); Gill and others (2002) CP101,606…”
Section: Ischemia Trauma and Epilepsy: Conditions Of Acute Cell Lossmentioning
confidence: 99%
See 1 more Smart Citation